People Analytics applied in a transport and logistics company - Godinho, Amanda Aguilar (2022)
The present study aimed to apply people analytics to analyze a set of variables of a specific group of employees, more specifically, drivers of a logistics company, in order to identify patterns and propose improvement strategies related to people management. The clustering technique was applied, from which the formation of two groups was obtained: the Senior and the Junior. Based on the characteristics of each one, such as age, time spent working and driving, productivity, number of overtime hours, absenteeism, it was possible to draw specific suggestions for each of the profiles.